2012
DOI: 10.4081/pmc.2012.73
|View full text |Cite
|
Sign up to set email alerts
|

Testicular microlithiasis and leydig cell proliferation in wistar rats underwent fowler-stephens procedure

Abstract: Microlithiasis and Leydig cell hyperplasia seem to have causative relation in operated undescended testis and present serious postoperative complications, with a review in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It is noted that testicular microliths do not typically affect Leydig cells, and maybe associated with Sertoli cell dysfunction ( 19 ). However, there is some evidence that microliths are associated with Leydig cell hyperplasia in rats ( 22 ). They are seen more frequently in children with Down syndrome and associated with testicular torsion, varicocele, retractile testes, cryptorchidism, inguinal hernias, and testicular neoplasms, though there is no evidence that they are premalignant ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that testicular microliths do not typically affect Leydig cells, and maybe associated with Sertoli cell dysfunction ( 19 ). However, there is some evidence that microliths are associated with Leydig cell hyperplasia in rats ( 22 ). They are seen more frequently in children with Down syndrome and associated with testicular torsion, varicocele, retractile testes, cryptorchidism, inguinal hernias, and testicular neoplasms, though there is no evidence that they are premalignant ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gougoudi et al 20 show microlithiasis on testicular ultrasound examination of Wistar rats underwent Fowler-Stephens procedure.…”
Section: Discussionmentioning
confidence: 99%
“…While observed in some cases ( 25 , 26 ), hydrocele is not a common cause of testicular microlithiasis ( 27 ). Microlithiasis has also not been reported in patients with LH-activating mutations; Gougoudi et al ( 28 ) reported that testicular microlithiasis co-existed with Leydig cell hyperplasia in Wistar rats. Thus, whether Leydig cell hyperstimulation in our patient is the cause of microlithiasis or not is not known.…”
Section: Discussionmentioning
confidence: 99%